Moving beyond Goffman: The performativity of anonymity on social networking sites - Murphy, Stephen (My University, 2019)
This paper aims to explore consumer behaviour on the popular anonymous social networking site (SNS) Yik Yak. It examines the reasons behind the turn to anonymous social networking and also considers the ways in which anonymity impacts consumers? self-performances on SNS. Design/methodology/approach The study used a netnographic approach to explore Yik Yak across eight universities in Ireland and the UK. Data are based on observation and participation on the app. Screenshots on smart phones were the central method used to collect data. Data also included 12 in-depth interviews. Findings Young consumers are becoming fatigued by the negative effects of self-presentation on many SNS. By enabling consumers to engage in what they consider to be more authentic modes of being and interaction, Yik Yak provides respite from these pressures. Through the structures of its design, Yik Yak enables consumers to realise self-authentication in anonymised self-performances that engender a sense of virtue and social connection. Practical implications This research highlights the potential value of anonymous SNS in fostering supportive dialogue, concerning mental health amongst post-millennials. Originality/value By invoking a performative lens, this paper extends a novel theoretical approach to understandings of identity formation within consumer research. By highlighting anonymity as a dynamic process of socio-material enactments, the study reveals how consumers? self-performances are brought into effect through the citation of various discursive arrangements, which promulgate distinct understandings of authenticity.
PUBLISHED
Keywords: Authenticity; Performativity; Social networking sites (SNS); Anonymity; Facebook fatigue; Netnography; Digital Engagement; Digital Humanities; Inclusive Society; Telecommunications; Consumer behaviour, society; Culture; Social exclusion; Social participation